2015
DOI: 10.4062/biomolther.2015.022
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of GABA from Fermented Rice Germ Ameliorates Caffeine-Induced Sleep Disturbance in Mice

Abstract: γ-Aminobutyric acid (GABA), a major inhibitory neurotransmitter in the mammalian central nervous system, is involved in sleep physiology. Caffeine is widely used psychoactive substance known to induce wakefulness and insomnia to its consumers. This study was performed to examine whether GABA extracts from fermented rice germ ameliorates caffeine-induced sleep disturbance in mice, without affecting spontaneous locomotor activity and motor coordination. Indeed, caffeine (10 mg/kg, i.p.) delayed sleep onset and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Some crude drugs contained in YKSCH (Bupleurum root, Japanese angelica root, and Cnidium rhizome) are reported to have compounds that bind to the GABA binding sites of the GABA A receptor in a receptor binding assay (25). According to previous studies, oral administration of GABA prolonged pentobarbital-induced sleep duration in group-housed mice (26). Though Yokukansan includes water-soluble botanic GABA (27), orally administered GABA does not cross the blood-brain barrier efficiently, and YKSCH treatment could not prolong the sleeping time in group-housed mice (Figure 2).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Some crude drugs contained in YKSCH (Bupleurum root, Japanese angelica root, and Cnidium rhizome) are reported to have compounds that bind to the GABA binding sites of the GABA A receptor in a receptor binding assay (25). According to previous studies, oral administration of GABA prolonged pentobarbital-induced sleep duration in group-housed mice (26). Though Yokukansan includes water-soluble botanic GABA (27), orally administered GABA does not cross the blood-brain barrier efficiently, and YKSCH treatment could not prolong the sleeping time in group-housed mice (Figure 2).…”
Section: Discussionmentioning
confidence: 75%
“…This is a Japanese language translation/reprint of 不 眠 モデルマウスに する抑肝散加陳皮半夏の 果 originally published in phil 漢方 (phil Kampo) 70, [26][27]2018…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Sedative-hypnotics or anti-anxiety agents have also been shown to increase pentobarbital-induced sleep duration ( Ma et al ., 2008 ). Treatment with caffeine, however, suppresses the expression of GABAergic systems and results in sleep disturbances ( Mukhopadhyay and Poddar, 2000 ; Li et al ., 2004 ; Mabunga et al ., 2015 ). In this study, we demonstrate that administration of caffeine (50 mg/kg) causes significant sleep disruptions during the pentobarbital-induced sleep test.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, caffeine also induces several adverse behavioral effects, including convulsive activity, the promotion of wakefulness, and locomotor stimulation even at relatively low doses ( Garrett and Holtzman, 1994 ). Additionally, the acute or chronic intake of caffeine in order to improve daily performance is commonly associated with sleep disturbances and insomnia, as well as other side effects including cardiovascular problems ( Mabunga et al ., 2015 ). In particular, previous studies have shown that caffeine exerts an allosteric effect on the γ-aminobutyric acid (GABA) A receptors and that it may reduce GABA neurotransmitter levels in the central nervous system (CNS) ( Kardos and Blandl, 1994 ; Fredholm et al ., 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several phytochemicals that are obtained from rice germs have been extensively utilized in medications, health and functional foods, cosmetics and food additives that include GABA (Mabunga et al, 2015;Shizuka et al 2004;Yoto et al, 2012) and γ-oryzanol (Wilson et al, 2007). Further, the nutritional values of some of the bioactive constituents found in rice germ are enhanced following fermentation (McGovern et al, 2004), for instance, α-ethylglucoside contained in fermented rice germ, is reported to prevent ultraviolet Bmediated disorder of epidermal permeability barrier (Hirotsune et al, 2005).…”
Section: Introductionmentioning
confidence: 99%